2017
DOI: 10.1016/j.jvs.2017.06.108
|View full text |Cite
|
Sign up to set email alerts
|

Midterm and long-term follow-up in competitive athletes undergoing thoracic outlet decompression for neurogenic thoracic outlet syndrome

Abstract: At our center, >40% of patients requiring FRRS for NTOS are competitive athletes. The results of this study show that the majority of them are able to return to their precompetitive state after FRRS, and few experience limitations in their daily living activities. Half can return to competition at or exceeding their premorbid ability level within 6 months of surgery. The majority are pleased with their decision to undergo FRRS. Further investigation is needed to identify predictive factors for successful retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
1
28
0
2
Order By: Relevance
“…Individuals who participate in high-level repetitive physical activity involving the upper extremity have an increased risk of developing TOS. Previous reports have linked TOS to high-performance athletes who engaged in repetitive overhead motions, such as baseball pitchers, volleyball players, and swimmers [ 3 , 4 , 5 ]. High-performance musicians who play instruments with repetitive arm motions are at risk of developing similar musculoskeletal ailments and nerve entrapment syndromes commonly seen in athletes, with typical examples including carpal tunnel syndrome, ulnar neuropathy, and cubital tunnel syndrome [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who participate in high-level repetitive physical activity involving the upper extremity have an increased risk of developing TOS. Previous reports have linked TOS to high-performance athletes who engaged in repetitive overhead motions, such as baseball pitchers, volleyball players, and swimmers [ 3 , 4 , 5 ]. High-performance musicians who play instruments with repetitive arm motions are at risk of developing similar musculoskeletal ailments and nerve entrapment syndromes commonly seen in athletes, with typical examples including carpal tunnel syndrome, ulnar neuropathy, and cubital tunnel syndrome [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was the first study looking at MLB pitchers returning after surgical decompression and demonstrated that they had capabilities equivalent or better than their historical baselines-even prior to the onset of symptoms. Schutze et al reported similar satisfaction with outcomes in a survey of competitive athlete who had undergone surgical treatment for neurogenic TOS [28]. They surveyed 67 athletes ranging from 14 to 48 years old, at an average of 3.9 years post procedure.…”
Section: Discussionmentioning
confidence: 79%
“…In 232 competitive athletes with nTOS (mean age, 19 years; range, 13-67 years) undergoing first rib resection with scalenectomy, 63% of those played baseball or softball. 19 Similarly, of 27 high-performance athletes diagnosed with nTOS (average age, 19 years; range, 14-32 years) and seeking either conservative or surgical care, 15% of those included baseball players. 1 Conversely, the current study does not describe treatment options but does provide an objective clinical presentation of adolescent baseball players (age, 17.2 ± 2.3 years) who have been diagnosed with nTOS.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although less common (<1%), arterial TOS presentation involves digital ischemia, coldness, paresthesia, and pain in the hand, but pain is typically not found in the shoulder or cervical region. While any of the 3 presentations of TOS are possible in a baseball player, previous literature 1,19,22 supports a greater incidence of nTOS in these athletes.…”
mentioning
confidence: 91%